Neocucurbitacin D, a novel lactone-type norcucurbitacin as xanthine oxidase inhibitor from Herpetospermum pedunculosum. Issue 12 (17th June 2020) - Jiang, He-Zhong; Hu, Sha; Tan, Ren-Xiang; Tan, Rui; Jiao, Rui-Hua
Abstract: A novel lactone-type norcucurbitacin, designated as neocucurbitacin D (1 ), together with five known cucurbitane triterpenes were isolated from traditional Tibetan medicine "Se Ji Mei Duo", which is the seed of Herpetospermum pedunculosum (Ser.) C.B. Clarke. The structure of neocucurbitacin D was elucidated by spectroscopic analysis, including 2D NMR and X-ray techniques. Compounds 1–6 were screened for their xanthine oxidase (XOD) inhibitory activity. Compound 1, 2 and 4 exhibited significant XOD inhibition with IC50 values ranging from 10.16 to 18.41 μM. The absolute stereochemistry and XOD inhibitiory activity of lactone-type norcucurbitacins was reported firstly. Graphical Abstract: